'Capturing' queer lives and the poetics of social change. Issue 5 (2nd September 2016) - Lambert, Karen
Abstract: In this paper, I highlight the ways that poetic inquiry can provide a space for marginalized voices and make movements in social change. By deploying Judith Butler's theory of passionate attachments to analyse a poem crafted from interview text, I suggest that poetic inquiry can open up a space in which to challenge oppressive discourses and present different angles and new types of knowledge regarding what it is like to 'be' different (lesbian). In offering this alternative methodology for researching and representing 'queer' stories, I illuminate how important it is to provide a space for marginalized voices to be heard, documented and shared whilst simultaneously suggesting that such voices have the potential to resonate with the embodied experiences of all, thus generating a space for collective social change.